Variations in antimicrobial resistance genes present in the rectal faeces of seals in Scottish and Liverpool Bay coastal waters - Eleanor Watson; Scott Hamilton; Nuno Silva; Simon Moss; Craig Watkins; Johanna Baily; Thorsten Forster; Ailsa J. Hall; Mark P. Dagleish (Environmental Pollution, 2024)

Genetic Diversity in Marine Planktonic Ciliates (Alveolata, Ciliophora) Suggests Distinct Geographical Patterns – Data From Chinese and European Coastal Waters - Maximilian H. Ganser; Dominik Forster; Weiwei Liu; Xiaofeng Lin; Thorsten Stoeck; Sabine Agatha (Frontiers in Marine Science, 2021)
Unraveling geographic distribution patterns of planktonic protists is a central goal in marine microbial ecology. Using a novel combination of recently developed phylogenetic and network analyses on a V4 18S rDNA metabarcoding dataset, we here analyzed the genetic diversity of marine planktonic ciliate communities in Chinese and European coastal waters. Thereby, our approach provided an unprecedented perspective on geographic patterns inferred from ciliate genetic diversity and accomplished a very fine resolution down to single nucleotides within operational taxonomic units (OTUs). While most OTUs (87%) exclusively contained sequences of either Chinese or European origin, those OTUs detected in both regions comprised the vast majority of reads (84%). Phylogenetic analyses of OTUs belonging to the same taxon revealed genetically distinct clades that were geographically restricted to either Chinese or European coastal waters. The detection of signature nucleotides emphasized this genetic distinction of Chinese and European clades. Second-level clustering of OTUs and reference sequences in two selected taxa (the oligotrichid Spirotontonia and the tintinnid Tintinnidium ) revealed the presence of several potentially new species or ones lacking genetic reference data. Geographic patterns were also discovered by network analyses within 700 widespread and abundant OTUs; in 77 of these OTUs, European and Chinese sequences formed significantly assortative groups. These assortative groupings indicated a higher genetic similarity among sequences from the same region than between sequences from different regions. Our results demonstrate that detailed analyses of metabarcoding data down to single nucleotide differences expand our perception of geographical distribution patterns and provide insights into historic and ongoing effective dispersal in protists. The congruent discovery of geographic patterns at different levels of resolution (between and within OTUs) suggests that cosmopolitan distribution in marine planktonic ciliates is less common than previously postulated.

Aquatic food webs in deep temperate lakes: Key species establish through their autecological versatility - Zhishuai Qu; Dominik Forster; Estelle P. Bruni; Daniela Frantal; Barbara Kammerlander; Laura Nachbaur; Gianna Pitsch; Thomas Posch; Thomas Pröschold; Katrin Teubner; Bettina Sonntag; Thorsten Stoeck (Molecular Ecology, 2021)
Microbial planktonic communities are the basis of food webs in aquatic ecosystems since they contribute substantially to primary production and nutrient recycling. Network analyses of DNA metabarcoding data sets emerged as a powerful tool to untangle the complex ecological relationships among the key players in food webs. In this study, we evaluated co‐occurrence networks constructed from time‐series metabarcoding data sets (12 months, biweekly sampling) of protistan plankton communities in surface layers (epilimnion) and bottom waters (hypolimnion) of two temperate deep lakes, Lake Mondsee (Austria) and Lake Zurich (Switzerland). Lake Zurich plankton communities were less tightly connected, more fragmented and had a higher susceptibility to a species extinction scenario compared to Lake Mondsee communities. We interpret these results as a lower robustness of Lake Zurich protistan plankton to environmental stressors, especially stressors resulting from climate change. In all networks, the phylum Ciliophora contributed the highest number of nodes, among them several in key positions of the networks. Associations in ciliate‐specific subnetworks resembled autecological species‐specific traits that indicate adaptions to specific environmental conditions. We demonstrate the strength of co‐occurrence network analyses to deepen our understanding of plankton community dynamics in lakes and indicate biotic relationships, which resulted in new hypotheses that may guide future research in climate‐stressed ecosystems.

Is repeated pulmonary metastasectomy justified? - Céline Forster; Amaya Ojanguren; Jean Yannis Perentes; Matthieu Zellweger; Sara Federici; Thorsten Krueger; Etienne Abdelnour-Berchtold; Michel Gonzalez (Clinical & Experimental Metastasis, 2020)
Recurrence after pulmonary metastasectomy (PM) is frequent, but it is unclear to whom repeated pulmonary metastasectomy (RPM) offers highest benefits. Retrospective analysis of oncological and post-operative outcomes of consecutive patients who underwent PM from 2003 to 2018. Overall survival (OS) and disease-free interval (DFI) were calculated. Cox regression was used to identify variables influencing OS and DFI. In total, 264 patients (female/male: 114/150; median age: 62 years) underwent PM for colorectal cancer (32%), sarcoma (19%), melanoma (16%) and other primary tumors (33%). Pulmonary metastasectomy was approached by video-assisted thoracic surgery (VATS) in 73% and pulmonary resection was realized by non-anatomical resection in 76% of cases. The overall median follow-up time was 33 months (IQR 16–56 months) and overall 5-year survival rate was 62%. Local or distant recurrences were observed in 172 patients (65%) and RPM could be performed in 66 patients (25%) for a total of 116 procedures. RPM was realized by VATS in 49% and pulmonary resection by wedge in 77% of cases. In RPM patients, the 5-year survival rate after first PM was 79%. Post-operative cardio-pulmonary complication rate (13% vs. 12%; p = 0.8) and median length of stay (4 vs. 5 days; p = 0.2) were not statistically different between first PM and RPM. Colorectal cancer (HR 0.56), metachronous metastasis (HR 0.48) and RPM (HR 0.5) were associated with better survival. In conclusion, our results suggest that RPM offers favorable survival rates without increasing post-operative morbidity.

Improving eDNA‐based protist diversity assessments using networks of amplicon sequence variants - Dominik Forster; Guillaume Lentendu; Sabine Filker; Elyssa Dubois; Thomas A. Wilding; Thorsten Stoeck (Environmental Microbiology, 2019)
Summary Effective and precise grouping of highly similar sequences remains a major bottleneck in the evaluation of high‐throughput sequencing datasets. Amplicon sequence variants (ASVs) offer a promising alternative that may supersede the widely used operational taxonomic units (OTUs) in environmental sequencing studies. We compared the performance of a recently developed pipeline based on the algorithm DADA2 for obtaining ASVs against a pipeline based on the algorithm SWARM for obtaining OTUs. Illumina‐sequencing of 29 individual ciliate species resulted in up to 11 ASVs per species, while SWARM produced up to 19 OTUs per species. To improve the congruency between species diversity and molecular diversity, we applied sequence similarity networks (SSNs) for second‐level sequence grouping into network sequence clusters (NSCs). At 100% sequence similarity in SWARM‐SSNs, NSC numbers decreased from 7.9‐fold overestimation without abundance filter, to 4.5‐fold overestimation when an abundance filter was applied. For the DADA2‐SSN approach, NSC numbers decreased from 3.5‐fold to 3‐fold overestimation. Rand index cluster analyses predicted best binning results between 97% and 94% sequence similarity for both DADA2‐SSNs and SWARM‐SSNs. Depending on the ecological questions addressed in an environmental sequencing study with protists we recommend ASVs as replacement for OTUs, best in combination with SSNs.

Transition boundaries for protistan species turnover in hypersaline waters of different biogeographic regions - Sabine Filker; Dominik Forster; Lea Weinisch; Merit Mora‐Ruiz; Bernardo González; María Eugenia Farías; Ramon Rosselló‐Móra; Thorsten Stoeck (Environmental Microbiology, 2017)
Summary The identification of environmental barriers which govern species distribution is a fundamental concern in ecology. Even though salt was previously identified as a major transition boundary for micro‐ and macroorganisms alike, the salinities causing species turnover in protistan communities are unknown. We investigated 4.5 million high‐quality protistan metabarcodes (V4 region of the SSU rDNA) obtained from 24 shallow salt ponds (salinities 4%–44%) from South America and Europe. Statistical analyses of protistan community profiles identified four salinity classes, which strongly selected for different protistan communities: 4–9%, 14–24%, 27–36% and 38–44%. The proportion of organisms unknown to science is highest in the 14–24% salinity class, showing that environments within this salinity range are an unappreciated reservoir of as yet undiscovered organisms. Distinct higher‐rank taxon groups dominated in the four salinity classes in terms of diversity. As increasing salinities require different cellular responses to cope with salt, our results suggest that different evolutionary lineages of protists have evolved distinct haloadaptation strategies. Salinity appears to be a stronger selection factor for the structuring of protistan communities than geography. Yet, we find a higher degree of endemism in shallow salt ponds compared with less isolated ecosystems such as the open ocean. Thus, rules for biogeographic structuring of protistan communities are not universal, but depend on the ecosystem under consideration.

Marine protist diversity in E uropean coastal waters and sediments as revealed by high‐throughput sequencing - Ramon Massana; Angélique Gobet; Stéphane Audic; David Bass; Lucie Bittner; Christophe Boutte; Aurélie Chambouvet; Richard Christen; Jean‐Michel Claverie; Johan Decelle; John R. Dolan; Micah Dunthorn; et al. (Environmental Microbiology, 2015)
Summary Although protists are critical components of marine ecosystems, they are still poorly characterized. Here we analysed the taxonomic diversity of planktonic and benthic protist communities collected in six distant E uropean coastal sites. Environmental deoxyribonucleic acid ( DNA ) and ribonucleic acid ( RNA ) from three size fractions (pico‐, nano‐ and micro/mesoplankton), as well as from dissolved DNA and surface sediments were used as templates for tag pyrosequencing of the V4 region of the 18S ribosomal DNA. Beta‐diversity analyses split the protist community structure into three main clusters: picoplankton‐nanoplankton‐dissolved DNA , micro/mesoplankton and sediments. Within each cluster, protist communities from the same site and time clustered together, while communities from the same site but different seasons were unrelated. Both DNA and RNA ‐based surveys provided similar relative abundances for most class‐level taxonomic groups. Yet, particular groups were overrepresented in one of the two templates, such as marine alveolates ( MALV )‐ I and MALV‐II that were much more abundant in DNA surveys. Overall, the groups displaying the highest relative contribution were Dinophyceae, Diatomea, Ciliophora and Acantharia. Also, well represented were Mamiellophyceae, Cryptomonadales, marine alveolates and marine stramenopiles in the picoplankton, and Monadofilosa and basal F ungi in sediments. Our extensive and systematic sequencing of geographically separated sites provides the most comprehensive molecular description of coastal marine protist diversity to date.

Meta-analyses of environmental sequence data identify anoxia and salinity as parameters shaping ciliate communities - Dominik Forster; Anke Behnke; Thorsten Stoeck (Systematics and Biodiversity, 2012)

Assessment of transcriptomal analysis of varicella-zoster-virus gene expression in patients with and without post-herpetic neuralgia - G. H. Ashrafi; Esther Grinfeld; Paul Montague; Thorsten Forster; Alan Ross; Peter Ghazal; Fiona Scott; Judith Breuer; Roslyn Goodwin; Peter G. E. Kennedy (Virus Genes, 2010)

Genome-wide reduction in transcriptomal profiles of varicella-zoster virus vaccine strains compared with Parental Oka strain using long oligonucleotide microarrays - Esther Grinfeld; Alan Ross; Thorsten Forster; Peter Ghazal; Peter G. E. Kennedy (Virus Genes, 2009)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)